Implikasi Filsafat Ilmu dan Relevansinya dalam Kehidupan Sehari-Hari - Selfi Okta Rahmadini; Salwa Apriliza; Fadhila Isfa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the meaning of philosophy of science in everyday life and its relevance for individuals and society. Using qualitative research methods with a literature review approach, this research examines various sources that explain how the philosophy of science can be applied in real life contexts. Research shows that philosophy of science is not only an academic discipline, but also serves as a guide in decision making, ethical development, and self-understanding. Through the application of philosophical principles, individuals can make better moral choices, improve critical thinking skills, and build healthier interpersonal relationships. Additionally, this article highlights the importance of awareness of environmental desirability as part of the moral responsibility resulting from philosophical thought. Thus, the philosophy of science plays an important role in shaping human perspectives and actions in the complex modern era.